Tinjauan Yuridis Terhadap Proses Penyelesaian Sengketa Pembatalan Jual Beli Hak Atas Tanah Harta Bersama (Studi Kasus Di Pengadilan Negeri Surakarta) - Sadhewo, Adhimas Wahyu, Nuswardhani, S.H., S.U, Shallman Al Farizi, S.H., M.H. MKn (2015)
This study aimed to: know the judge in determining the evidence related to the dispute over the cancellation of the sale and purchase of land property rights along and knowing Judge consideration in decisions on disputes cancellation of the sale and purchase of land rights joint property. The method used is a method normative and descriptive approach. Sources of data in this study are secondary and primary data. On this case can be concluded Plaintiffs have managed to prove the argument of the lawsuit, while the Defendant I did not manage to prove rebuttal, that the sale and purchase of land in the Notary/PPAT conducted by the Plaintiff to Defendant I is null and void, because it was made/done in a way not legitimate by unlawfully selling is in the process of purchasing does not involve the defendant II which also still has the right to the land, and the land is a property that is still in dispute in the process of division. Keywords: Dispute Resolution Process, Cancellation of The Sale and Purchase of Land, and Community Property